Literacy for Peace: A Program to Prevent Bullying and Promote Positive Character in Elementary School - Winarto, Eline Rozaliya; Siti Nuraeni, Rani; Mayasari, Ria; Khairana, Rika; Hildayanti, Rima; Septiana, Risna; Meilin, Rizka Karima (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2025)
Bullying in schools can harm children' mental and emotional well-being and possibly result in poor character traits down the road. Bullying has negative effects on learning environments, trauma, and self-confidence. It is crucial to put bullying prevention into practice in order to address this problem. In the community, at school, and at home, literacy activities help youngsters develop morality and comprehend information. This community service was provided using an organized way during the PPL 1 Program at SDN Silih Asuh 2. Enhancing the pupils' literacy culture is the goal of this community service project. Through the